Ser estudante de Pós-graduação em tempos de bolsonarismo: analisando experiências diante do desmonte da pesquisa científica no Brasil - Costa, Felipe Franklin Anacleto da (2021)
In the 1990s, changes in the evaluation policies inaugurated a productivist and mercantile logic in Brazilian post-graduation studies. Despite the policies of expansion of higher education of the Petrobras governments, with greater investments in research funding agencies, this dynamic has not undergone major changes, promoting advances, but deepening various inequalities. The Bolsonaro government, in addition to deepening this logic, has mischaracterized the Brazilian university and graduate studies, reducing the public budget for education and research, implying the cut of graduate scholarships and the imminent risk of interruption of academic activities, elaborating projects of privatization of universities such as Future-se, disrespecting the university autonomy by appointing acting rectors, among other measures. Through semi-structured interviews, I carried out a comparative analysis between the experiences of students from graduate programs with concept 4, the minimum to have a doctorate course, based in UFPB, and graduate programs with concept 6 and 7, considered to be programs of excellence and international recognition, located in the South-Southeast axis. The courses chosen were Sociology (PPGS/UFPB and PPGS/UFRGS), Anthropology (PPGA/UFPB and PPGAS/USP) and Education (PPGE/UFPB and PPGE/UFMG) due to two factors: the greater proximity of the researcher with students and professors of these programs at UFPB and the relation of the object and the theoretical-methodological approaches of the research with these areas. In this way, 12 students were interviewed, two from each program, one from the master's program and another from the doctoral program, seven women and five men. I present the results around three axes: 1) relationships with the graduate program, and 2) mental health, self-care strategies and resistance to the current situation.